Hubungan Motivasi Dan Sikap Bidan Dengan Kelengkapan Pengisian Lembar Mtbs Di Puskesmas Kabupaten Karanganyar - Radiyanti, Debby Cintia Ayuning, Anisa Catur Wijayanti, SKM., M.Epit, Purwanti, SKM., M.Kes (2016)
The pattern of diseases in infants in Karanganyar namely pneumonia. The number of cases of pneumonia toddlers are found and dealt with in 2014 as many as 726 cases, an increase over the year 2013 as many as 647 cases. One of the approaches used to improve quality and access to health services for infants and toddlers is done through the implementation of IMCI program. One key to the success of the IMCI program that is characterized by the compliance officer in the completeness and consistency of form filling. The purpose of this study to determine the relationship between motivation and attitude of midwives by charging sheet IMCI in Health Center Karanganyar. This research method uses design of observational analytic cross sectional approach. The sample in this study is the midwife as many as 77 people. Using Chi Square statistical test by using computer applications. The results showed that there was a relationship with a midwife motivation completeness sheet IMCI p-value of 0.011 (POR = 3.333; 95% CI: 1.293 to 8.591); attitude midwife with a complete sheet IMCI p-value 0.002 (POR = 4.276; 95% CI: 1.643 to 11.129).